Transmission electron microscopic observations of the multilevel microstructure of crosslinked copolymers with methacrylates and siloxane macromers by a radically polymerizable tuning approach. Issue 5 (19th May 2012) - Yokota, Mitsuru; Ajiro, Hiroharu; Akashi, Mitsuru
Abstract We investigated by Transmission Electron Microscopy (TEM) the morphologies of crosslinked copolymers from methacrylate monomers from methylmethacrylate (MMA) and trifluoroethylmethacrylate (TFEMA), polydimethylsiloxane (PDMS) macromers with molecular weight (Mn) of 1, 700 and 4, 700 g/mol, and crosslinker. Depending on the PDMS content, we observed, spherical PMMA islands in which small PDMS domains were dispersed, PMMA continuous phase, closely packed PTFEMA islands, and homogeneously dispersed PDMS domains were observed with low or middle magnification. Fine observation at 100, 000‐fold magnification revealed the "fundamental" common size domain, which was determined by the Mn value of the PDMS macromer. Thus we found two microstructure types: (1) a "fundamental domain" due to the Mn of the PDMS macromer, and (2) an aggregated domain. The former was constant under all conditions, but the latter was affected by the comonomer and its ratio. The present results are essential in understanding the chemical and physical characteristics of crosslinked copolymers from PDMS macromers. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013